RE-BRANDING KEMASAN & LOGO KOPI KUDA BERKAIT DESA SEBONG PEREH - Alamsyahbana, M. Isa; Nursyalim, Alwi Dwi; Mareta, Karina Vivinanda; Pramita, Maharani Eka; Gunawan, Syahrul; Audina, Yulia Putri (Jurnal Pengabdian, Pembelajaran dan Pemberdayaan Ekonomi Masyarakat (JP3EM), 2025)
Sebong Pereh Village is a coastal village in kecamatan, Teluk Sebong , Kabupaten Bintan , Provinsi Kepulauan Riau . This research was carried out for the first time on October 23 2023, making Kopi Kuda Berkait which is located in Sebong Pereh Village at Mr Bedu's house as the owner of the Kopi Kuda Berkait business. We are carrying out a program, namely Re-Branding. There we asked about the history of the formation of related horse coffee and the obstacles experienced, especially in legality, namely the HALAL, PIRT and BPOM labels on the packaging of the related horse coffee, and another obstacle, namely the ingredients in the seahorse coffee mixture. Before the rebranding process, Kopi Kuda Berkait's packaging and logo had an appearance that was considered less attractive. The packaging uses matte black and a logo design that is considered less attractive. After going through a rebranding process, Kopi Kuda Berkait now has significant changes to its packaging and logo. Attractive colors are now used, with the front of the packaging being transparent, allowing buyers to clearly see the Kuda Berkait Coffee powder inside. Meanwhile, the back of the packaging is decorated in gold, giving an elegant and exclusive impression. This change is expected to provide a stronger appeal to consumers and reflect better quality and brand identity after the rebranding process. In addition, using ziplock packaging can protect the Kuda Berkait Coffee powder from exposure to air which can affect the quality of the aroma and taste.